Assessment of rice water requirements under Inceptisol in Raipur district using CROPWAT 8.0 - JANGRE, NILIMA; SINHA, JITENDRA; KUMAR, FANESH; RAJ, JEET (Journal of Soil and Water Conservation, 2023)
Water is the most important input for agriculture and its judicious use and efficient delivery is the need of the hour. Legitimate information on evapotranspiration, crop water requirements, and net irrigation requirements is required for the effective planning of this resource. The present research focuses on estimation of Crop Water Requirement for the rice crop under Inceptisol in Raipur district using CROPWAT 8.0 model. 21-years climatic data were analysed with the CROPWAT model, which is based on the United Nations Food and Agriculture Organization (FAO) paper number 56 (FAO 56). The Penman- Monteith method was used to estimate reference evapotranspiration (ET0). Crop coefficient (Kc) from the phenomenological stage (initial, development, mid-season, and late-season) of rice were applied to adjust and estimate the actual evapotranspiration ETc through a water balance of the irrigation water requirements (IR). In this study as per the local conditions of the rice crop, a fixed percentage method has been adopted and effective rainfall has been considered as 80% of rainfall. The total average effective rainfall in the Raipur district has been computed as 886.32 mm. The average reference crop evapotranspiration (ETc) during the 21 years period was found to be 575.64 mm. It varies from 513.2 mm to 639.6 mm. The average irrigation requirement for rice crops during the period from 23rd June to 14th November was 362.53 mm. Water requirement of rice as per the field condition varies from 1192.3 to 1317.9 mm also including application losses and special needs.